DAR strategy, with a neuroscientific approach, improves the critical thinking of higher education student (LACCEI, 2024)
This article shows the most relevant of the research, whose objective was to determine the influence of the DAR strategy: deconstruction, abstraction and reconstruction with a neuroscientific approach for the improvement of critical thinking. The theoretical foundation lies in cognitive neuroscience, brain plasticity, cognition and long-term memory. A quasi-experimental design was chosen for a sample of 48 students of Initial Teacher Training - FID of Primary Education. For data collection, an observation sheet was constructed and applied, which served to quantify the dependent variable: critical thinking. This instrument was validated by expert judgment and, for its reliability, Cronbach's alpha coefficient was produced. The results show that a large percentage of students in the experimental and control groups were located in the level in process, before the application of the stimulus. However, after it was applied, a large percentage of the experimental group was located in the achieved and outstanding levels while the results of the control group remained unchanged compared to the pretest. The hypothesis was also tested using the Mann-Whitney U test, obtaining a value of (p-value =0.000), indicating a significant difference in the arithmetic means between the GE and CG therefore, the null hypothesis was rejected and the research hypothesis was recommended.